الدعوة إلى تيسير النحو العربي البواعث والمنطلقات - د. سفيان بلعجين (Annales du Patrimoine, 2018)
يسعى هذا البحث إلى معالجة قضية لغوية مهمة وهي الدعوة إلى تيسير النحو العربي، باعتبارها رد فعل لما شهده هذا البحث العلمي الأساسي من تعقيد وتشعّب، جرّاء تعدّد المدارس النحوية والاختلاف بين علمائها، ما أدى إلى تعقيد القواعد وخلق صعوبة في تلقين النحو واكتسابه، فظهرت منذ القديم محاولات لتيسير النحو وتبسيطه بداية بإعداد المختصرات، مرورا بدعوة أهم علماء الدرس اللغوي القديم من أمثال الجرجاني إلى ذلك، وبخاصة في الأندلس مع ابن مضاء القرطبي الذي ثار على نظرية العامل لتعقديها، وظهرت المنظومات النحوية التي جاءت لتسهيل حفظ القواعد، لتزداد الدعوة إلى تيسير النحو مع الدراسات اللغوية واللسانية العربية الحديثة، حتى وصل الأمر بالبعض أن دعا إلى إلغاء الإعراب محتجين بأنّه الركيزة الأولى للنحو المعقّد. - This research seeks to address an important linguistic issue, which is the call to facilitate Arabic grammar, as a reaction to the complexity of this basic scientific research, due to the multiplicity of grammatical schools and the difference between their scholars. This complicated the rules and created difficulty in learning and acquiring grammar, Since ancient times, there have been attempts to facilitate and simplify grammar, beginning with the preparation of acronyms, passing through the invitation of the most important scholars of the ancient linguistic lesson, such as Al-Jurjani, Especially in Andalusia with Ibn Madhâ' al-Qurtubi, who rebelled against the theory of the factor because of its complexity. Grammatical systems appeared that came to facilitate the memorization of grammar, and the call for facilitating grammar increased with modern Arabic linguistic and linguistic studies. Some even called for the abolition of parsing, arguing that it was the first pillar of a complex grammar. - Dr Sofiane Beladjine - University Center of Relizane, Algeria